Eliminación de ruido impulsivo en imágenes a color, utilizando interpolación con funciones de base radial - Echeverri Arias, Jaime Alberto; Rudas Castaño, Jorge Eliécer; Toscano Cuello, Ricardo; Ballesteros Padilla, Rubén (Ingeniería, 2011)
This paper presents a method for impulsive noise elimination in colored images by using interpolation through radial basis functions. This is a classic problem in many applications in different fields; its origin lies in defective-data capturing mechanisms that make errors at different time intervals over an input signal. We compare the results obtained using the proposed method to the resultes obtained using classical non-linear filtering algorithms, such as the median filtering, and the mean and outlier filtering. In all scenarios, the results were more effective when using the proposed method. The algorithm proved to be robust under hihg-noise conditions during the tests. The results were analyzed using Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR), which are two commonly used metrics to compare the quality between two images after performing a restoration process. MSE of 14 and PSNR of 35.8 db were reached on the 512x512-pixel Lenna image with a noise-pixel percentage of 40%.